Optimizing Discord Application to The students’ Vocabulary Enhancement In Synchronous Learning - Rahman, Fikri Abdu; Akib, Erwin; Junaid (Journal of Computer Interaction in Education, 2020)
This research focused in optimizing the Discord application to enhance students' vocabulary in synchronous learning. The method used in this research was pre-experimental research method with one group pre-test and post-test design, and the data were collected by giving pre-test and post-test. The sample of this research was class VII A of SMP Negeri 5 Mandai. The sample consisted with 27 students. The population of this research was the first-grade students of SMP Negeri 5 Mandai which consisted of 297 students in the academic year of 2021/2022. The sample was taken by purposive sampling technique to select the sample. The technique used for obtaining data was vocabulary test. The research findings showed that the mean score of the students in vocabulary was proved by post-test 72,77 was higher than the mean score of pre-tests 64,07. Furthermore, by the result of the hypothesis t-test value was 11,126 which mean higher than t-table 2,056. It means that H1 was accepted and H0 was rejected. Based on the findings that there was significance difference between the result of pre-test and post-test. Eventually, optimizing Discord application to the students’ vocabulary enhancement in synchronous learning was excellent to applied to the further research.